2022
DOI: 10.3390/plants11111481
|View full text |Cite
|
Sign up to set email alerts
|

Genome Size Variation in Dianthus sylvestris Wulfen sensu lato (Caryophyllaceae)

Abstract: Genome size (GS) is an important characteristic that may be helpful in delimitation of taxa, and multiple studies have shown correlations between intraspecific GS variation and morphological or environmental factors, as well as its geographical segregation. We estimated a relative GS (RGS) of 707 individuals from 162 populations of Dianthus sylvestris with a geographic focus on the Balkan Peninsula, but also including several populations from the European Alps. Dianthus sylvestris is morphologically variable s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 94 publications
2
15
0
Order By: Relevance
“…Finally, for S. benthamiana and S. ericoides , despite a high phylogenetic relatedness, they can preserve the status of species thanks to clear morphological and ecological differentiation. The patterns detected in this study are in accordance with the rich literature available for recently diversified plant species in the Mediterranean Basin (De Castro et al, 2015; Bateman, 2018; Liu et al, 2022; Terlević et al, 2022). Indeed, the Mediterranean region is one of the most important hotspots for biodiversity, and the factors that have driven plant speciation are many and are related to its complex climatic and geologic history (Greuter, 1991; Cañadas et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Finally, for S. benthamiana and S. ericoides , despite a high phylogenetic relatedness, they can preserve the status of species thanks to clear morphological and ecological differentiation. The patterns detected in this study are in accordance with the rich literature available for recently diversified plant species in the Mediterranean Basin (De Castro et al, 2015; Bateman, 2018; Liu et al, 2022; Terlević et al, 2022). Indeed, the Mediterranean region is one of the most important hotspots for biodiversity, and the factors that have driven plant speciation are many and are related to its complex climatic and geologic history (Greuter, 1991; Cañadas et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…4). This finding agrees with data obtained from research carried out on Balkan taxa belonging to the D. virgineus complex, where the segregation of different systematic units was inferred to be reliant on combined geographical and ecological gradients (Terlević & al., 2022, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the name Dianthus sylvestris Wulfen, originally described from Slovenia (Domina & al., 2021a), would apply to the “Balkan” lineage. Karyological (Terlević & al., 2022), morphological (Terlević & al., 2023), and genetic variation have been investigated within the Balkan D. sylvestris , which may lead to some further taxonomic adjustments. Similarly, integrative taxonomic studies are ongoing within the Apennine (and Central Mediterranean) D. virgineus , in light that 21 taxonomically doubtful taxa have been described in this area based solely on morphological qualitative features.…”
Section: Discussionmentioning
confidence: 99%
“…sylvestris is one of the metallophytes present at Cu‐contaminated alpine locations around Monte Avanza mine. The native distribution of this small shrub ranges from NW and central Alps to W and N Greece, where it mainly occurs at uncontaminated sites in temperate biome (Fassou et al 2022, Terlević et al 2022) but occasionally can be found on metalliferous soils (Punz and Mucina 1997). Our preliminary survey of Monte Avanza vegetation identified D. sylvestris subsp.…”
Section: Introductionmentioning
confidence: 99%